Clinical Prognostic Factors Predicting Survival of Motor Neuron Disease Patients with Gastrostomy - Yang, Jie (Curtin University, 2024)
This thesis utilises a retrospective observational study to investigate factors associated with longer survival in MND patients post gastrostomy. Collectively, factors such as age, weight loss, non-invasive ventilation use, and phase angle from the bioelectrical impedance analysis were associated with survival. The findings will inform future guidelines for gastrostomy in MND, enhancing patient care. Future studies could build on these findings by exploring factors associated with survival beyond 12 months post gastrostomy.